IDENTIFIKASI KERUSAKAN TUMBUHAN DI KEBUN RAYA BALI OLEH BENALU - Sunaryo, Sunaryo (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
The mistletoes of Dendrophthoe pentandra, Helixanthera cylindrica,Scurrula parasitica and Scurrula atropurpurea growing on several plantscollection in Bali Botanical Gardens. The research was carried out inJune 2007 found about 114 branches/twigs of 105 treee collections hadbeen attacked by several mistletoes. The attacked trees consisted of51 species belong to 24 genera. The tree collections of genus Syzygium,Familie Moraceae were the most frequent tree species being attackedby the mistletoes. Dendrophthoe pentandra was the most frequentmistletoe attacking the botanic gardens plant collections and causedthe biggest damaging effect. The damaging effect of the parasiticmistletoes generally occurred on the distal part of infected branches ortwigs of the host plants.